Penal Code, ch. 43, §§ 547, MONTGOMERY, CODE OF ORDINANCES 213, 223-29 (1888 Brown Printing Co.) (Montgomery, Alabama). - (:unkn) unknown (General Publisher, 1888)
Any person who fires or discharges, or causes to be fired or discharged, any pistol, gun, cannon, anvil, or anything of like kind or character, without the permission of the city council of Montgomery; or who lets off or discharges any rocket, fire-crackers, squib or other fire-works, without first having obtained permission of the mayor, who shall designate the place where such firing may be done, must, on conviction, be fined not less than one nor more than one hundred dollars.
--
Keywords: DISCHARGE